To assess the diagnostic accuracy of LRINEC Score for prediction of necrotizing fasciitis in patients presenting with clinical skin and subcutaneous tissue infections - Riaz Shahid, Muhammad; Ghani, Usman; Ashraf, Muhammad Ayub; Rashid, Fahd; Shahid, Muhammad; Khattak, Fahim (Infectious Diseases Journal of Pakistan, 2024)
Background: Necrotizing fasciitis is an inflammatory disease that causes the skin, soft tissues, and fascia to break down. A strain of Streptococcus pyogenes bacteria is frequently the source of it, however mixed infections involving coliforms, anaerobes, and Gram-negative bacteria can also be to blame. Even with contemporary medical care, necrotizing fasciitis is associated with a significant fatality rate. The objective of this study is to determine the diagnostic accuracy of the Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) score for predicting necrotizing fasciitis in patients with cutaneous and subcutaneous tissue infections. Material and Methods: This Cross-sectional study was conducted at Combined Military Hospital, Rawalpindi from May 2021 to October 2022. Hundred cases of probable necrotizing fasciitis coupled with clinical cutaneous or subcutaneous infections were included. They underwent clinical examinations and blood investigation (Sodium, Hemoglobin, total white cell count, Glucose, Creatinine, C-reactive protein (CRP), and biopsy for histopathology). Patients under the age of 15 or older than 75, with soft-tissue infections, undergone surgical debridement and without the result of CRP in the initial 48 hours of retention were excluded. LRINEC score ≥6 was used for labelling a case with necrotizing fasciitis. LRINEC score was then compared with results of histopathology and sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated using SPSS version 23. Results: 35 (35%) out of total belonged to the age group between 46-55 years. Male and female ratio were 64 (64%) and 36 (36%). Diabetes mellitus was the most common etiological cause occurring in 56 (56%) patients. The sensitivity of the LRINEC scoring system was 79.7% and the specificity noted was 87.8%. The PPV was 90.4% and the NPV came out to be 75%. Conclusions: LRINEC scoring system has a significant sensitivity and reasonable specificity in diagnosing cases of Necrotizing fasciitis among patients with severe soft-tissue infection. LRINEC score can be used for predicting the outcome of such cases. Keywords: Laboratory risk indicator for necrotizing fasciitis (LRINEC), Necrotizing fasciitis, Subcutaneous tissue infections